Storing Authenticity at the Surface and into the Depths: Securing Paper with Human- and Machine-Readable Devices - Kaminska, Aleksandra (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2018)
This article examines the media technologies that mark paper as authentic. Using the examples of passports and paper banknotes, it considers the security features (e.g. graphic marks, holographs, chips) that do the work of reliably storing, protecting, and communicating authenticity across both space and time. These overt and covert authentication devices are examined in two interconnected ways: 1) as technologies with specific temporal conditions, constrained both by technical longevity and functional lifespan; and 2) as technologies that must be continuously reinvented to outpace counterfeiters and forgers. Together, these attributes have led to strategies of concealment that shift authentication from a human-legible activity at the perceptible surface to one that is concealed in the depths of machine readability. While this adds a level of security, it is also an example of how the material environment becomes rich in information that is inaccessible to human processing.